Effects of Tool Novelty and Action Demands on Gaze Searching During Tool Observation - Tamaki, Yoshinori; Nobusako, Satoshi; Takamura, Yusaku; Miyawaki, Yu; Terada, Moe; Morioka, Shu (Frontiers in Psychology, 2020)
Technical reasoning refers to making inferences about how to use tools. The degree of technical reasoning is indicated by the bias of the gaze (fixation) on the functional part of the tool when in use. Few studies have examined whether technical reasoning differs between familiar and unfamiliar novel tools. In addition, it has not been determined what effect the intention to use the tool has on technical reasoning. This study examined gaze shifts in relation to familiar or unfamiliar tools, under three conditions (free viewing, lift, and use), among 14 healthy adults (mean age ± standard deviation, 29.4 ± 3.9 years). The cumulative fixation time on the functional part of the tool served as a quantitative indicator of the degree of technical reasoning. The two-way analysis of variance for tools (familiar and unfamiliar) and conditions (free viewing, lift, and use) revealed that the cumulative fixation time significantly increased under free viewing and use conditions, compared to lift conditions. Relative to the free viewing condition, cumulative fixation time for unfamiliar tools significantly decreased in the lift condition and significantly increased in the use condition. Importantly, the results showed that technical reasoning was performed in both the use and the free viewing conditions. However, technical reasoning in the free viewing condition was not as strong as in the use condition. The difference between technical reasoning in free viewing and use conditions may indicate the difference between automatic and intentional technical reasoning.